A nitrogen dynamic hydroponic culture on performance and quality of water spinach (Ipomoea aquatica). (2nd April 2020) - Xiang, Shuyu; Wu, Songheng; Zhang, Qi; Liu, Yuhuan; Ruan, Roger
Abstract: In view of the unreasonable application of chemical fertilizers in agriculture and the groundwater pollution caused by nitrogen (N) leaching, a nitrogen dynamic hydroponic culture was used to simulate the dynamics variation of ammonium nitrogen (NH4 -N) and nitrate nitrogen (NO3 -N) in the leaching loss soil. Solutions with different ratio of NO3 -N and NH4 -N (100:0, 70:30, 50:50, 30:70 and 0:100) were prepared as well as the same solutions that not containing NO3 -N .Water spinach was chosen to culture in the two solutions that differ from NO3 -N every two (E2) or five days (E5) to observe the growth, quality and nutrient solution uptake. In terms of the growth, uptake of N source, N use efficiency and the chemical indicators, plants grown in the balanced solution all showed the best results. The nitrogen dynamic hydroponic culture showed some differences between E2 and E5 in some aspects. Under the same N source level, plants in E2 showed a better growth and higher NO3 -N uptake than E5. On the other hand, the uptake of NH4 -N seemed to be affected significantly by the interchanged frequency, which showed the same variations of glutamine synthetase activity. The activity of nitrate reductase and glutamine synthetase showed the coexist of NO3 -N and NH4 -N could play synergistic effect. It is not recommended to supplement NO3 -N frequently in the case of N leaching loss, which has little impact on the growth and may lead to the hard taste and groundwater pollution.